Pulmonary arterial hypertension-related myopathy: an overview of current data and future perspectives - Marra, Alberto M.; Benjamin, Nicola; Grünig, Ekkehard (Nutrition, metabolism and cardiovascular diseases, 2015)
BACKGROUND AND AIM: Exercise intolerance is one of the key features of pulmonary arterial hypertension (PAH). The main determinants of exercise impairment include hypoxemia, reduced right ventricular output, perfusion/ventilation mismatch, and weakness of skeletal and breathing muscles. The aim of the current review is to describe the findings in the existing literature about respiratory and muscle dysfunction in PAH. Animal and clinical studies regarding both respiratory and peripheral skeletal muscles and the effect of exercise training on muscle function in PAH patients are analyzed. DATA SYNTHESIS: PAH myopathy is characterized by reduced skeletal muscle mass, reduced volitional and non-volitional contractility, reduced generated force, a fiber switch from type I to type II, increased protein degradation through ubiquitin-proteasome system (UPS) activation, reduced mitochondrial functioning, and impaired activation-contractility coupling. Increased inflammatory response, impaired anabolic signaling, hypoxemia, and abnormalities of mitochondrial function are involved in the pathophysiology of this process. Exercise training has been shown to improve exercise capacity, peak oxygen uptake, quality of life, and possibly clinical outcomes of PAH patients. CONCLUSIONS: The skeletal muscles of PAH patients show a wide spectrum of cellular abnormalities that finally culminate in muscle atrophy and reduced contractility. Exercise training improves muscle function and bears a positive impact on the clinical outcomes of PAH patients.